The Influence of Transformational Leadership and Employee Competence on Employee Performance with Work Motivation as an Intervening Variable: JEL Classification: M12, M54, J24, J28, C83 - Arief Bangsawan Aldo; Yudi Sutarso (Journal La Bisecoman, 2026)
In the era of globalization, organizations are required to possess competent human resources and effective leadership in order to enhance employee performance, which serves as a primary indicator of organizational success. PT Kimia Farma Diagnostika, West Java Business Unit 1, as a healthcare service provider, faces challenges in strengthening transformational leadership, employee competence, and work motivation to achieve optimal performance outcomes. This study aims to analyze the influence of transformational leadership and employee competence on employee performance, with work motivation functioning as an intervening variable. The research adopts a quantitative approach with an explanatory research design. The population consists of 152 employees, with a sample of 110 respondents determined through simple random sampling using the Slovin formula (α = 5%). Data were collected using a seven-point Likert scale questionnaire and analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares using SmartPLS 4. The findings indicate that transformational leadership exerts a positive and statistically significant effect on employee performance (β = 0.144; p = 0.027) and work motivation (β = 0.426; p < 0.001). Employee competence also demonstrates a positive and significant influence on performance (β = 0.539; p < 0.001) and work motivation (β = 0.558; p < 0.001). Work motivation significantly affects employee performance (β = 0.314; p < 0.001). Furthermore, work motivation is proven to significantly mediate the relationship between transformational leadership (β = 0.134; p = 0.001) and employee competence (β = 0.175; p = 0.004) on employee performance. The R² values ​​indicate a highly robust model, explaining 91.6% of the variance in work motivation and 95% of the variance in employee performance. These findings underscore the importance of strengthening transformational leadership and continuously developing employee competencies to enhance both motivation and performance.